Implementasi Pembiayaan Gadai Emas di BMT. UGT. Sidogiri Cabang Kangean Sumenep - Makhshushi Zakiyah; Zainul Anwar; Maila Maila (Mazinda : Jurnal Akuntansi, Keuangan, dan Bisnis, 2023)
Every Islamic financial institution has a varied marketing strategy to attract public interest. Both in terms of product and operational flow that is applied. As an Islamic financial institution that is not only profit-oriented, but also has a social mission to help those who are experiencing difficulties. BMT UGT Sidogiri prepares a financing product whose application is quite simple, namely the Sharia Gold Pawn (GES). So that the products are in great demand by the people of Kangean. This is what encourages researchers to find out how the GES financing product is implemented. This qualitative descriptive field research was conducted at BMT. UGT. Sidogiri Kangean Branch, using data obtained from primary and secondary data sources. Each field data was analyzed using a descriptive method and tested for its level of validity using triangulation (source) and observation extension methods. The conclusion obtained is that the implementation of BMT Sharia Gold Pawn financing. UGT. Sidogiri is in accordance with the terms and conditions. The application is easy, simple and fast, and is accompanied by rahn financing insurance.